Profile of D-dimer in Uncomplicated Pregnancy: Profile D-dimer Kehamilan tanpa Komplikasi - Rahajuningsih Dharma; Mercy T. Panjaitan; Kanadi Sumapradja; Rianto Setiabudy (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: To obtain the profile of D-dimer in uncomplicated pregnancy. Methods: A cross sectional study was done on 90 uncomplicated pregnant women consisted of 30 women in each trimester and 30 healthy, nonpregnant women as control group from July to August 2012. D-dimer level was measured by particle enhanced immunoturbidimetry method using Innovance D-dimer and Sysmex CA 1500 in the Department of Clinical Pathology, Dr. Cipto Mangunkusumo Hospital, Jakarta. Results: All women in the control group showed normal D-dimer level (<0.,5 mg/L FEU). The median and range of D-dimer level in the 1st trimester, 2nd trimester, and 3rd trimester were 0.42 mg/L FEU and 0.1-1.07 mg/L FEU, 0.97 mg/L FEU and 0.6-3.34 mg/L FEU, and 1.56 mg/L FEU and 0.69-3.75 mg/L FEU, respectively. Increased D-dimer level was found in 27% of pregnant women in 1st trimester, 87% in 2nd trimester, and 100% in 3rd trimester. Conclusion: Increased D-dimer level was found in 27% of pregnant women in 1st trimester, 87% in 2nd trimester, and 100% in 3rd trimester. The range of D-dimer level in the 1st trimester was 0.1-1.07 mg/L FEU, in the 2nd trimester was 0.6-3.34 mg/L FEU, and in the 3rd trimester was 0.69-3.75 mg/L FEU. Keywords: D-dimer, trimester, uncomplicated pregnancy Abstrak Tujuan : Untuk mendapatkan profil D-dimer pada kehamilan tanpa komplikasi. Metode : Penelitian potong lintang dilakukan pada 90 perempuan hamil tanpa komplikasi yang terdiri atas 30 perempuan pada tiap trimester dan 30 perempuan sehat yang tidak hamil, sebagai kelompok kontrol dari bulan Juli sampai Agustus 2012. Kadar D-dimer diukur dengan cara particle enhanced immunoturbidimetry menggunakan reagen InnovanceÃ’ D-dimer dan koagulometer SysmexÃ’ CA 1500 di Deparemen Patologi Klinik, Rumah Sakit Umum Pusat Nasional Dr. Cipto Mangunkusumo, Jakarta. Hasil: Seluruh perempuan dalam kelompok kontrol mempunyai kadar D-dimer dalam batas normal (<0.,5 mg/L FEU). Median (rentang) kadar D-dimer pada trimester pertama, kedua, dan ketiga berturut-turut 0.42 mg/L FEU (0.1-1.07 mg/L FEU), 0.97 mg/L FEU (0.6-3.34 mg/L FEU), dan 1.56 mg/L FEU (0.69-3.75 mg/L FEU). Peningkatan kadar D-dimer ditemukan pada 27% perempuan hamil trimester pertama, 87% trimester kedua, dan pada 100% trimester ketiga. Kesimpulan: Peningkatan kadar D-dimer ditemukan pada 27% perempuan hamil trimester pertama, 87% trimester kedua dan 100% pada trimester ketiga. Rentang kadar D-dimer level pada trimester pertama adalah 0.1-1.07 mg/L FEU, pada trimester kedua 0.6-3.34 mg/L FEU, dan pada trimester ketiga 0.69-3.75 mg/L FEU. Kata kunci: D-dimer, kehamilan tanpa komplikasi, trimester